PENERAPAN STRATEGI PEMBELAJARAN MAHASISWA PRODI PENDIDIKAN AGAMA ISLAM PADA SEKOLAH TINGGI AGAMA ISLAM NEGERI (STAIN) MALIKUSSALEH LHOKSEUMAWE - zulfikar ali buto (UIN Sumatera Utara Medan, 2017)
Learning strategy is structured these steps prepared by the faculty before making the learning process. Institutions School of Islamic Higher Learning Strategies include as one of the subjects that must be followed by every student, especially Programs Tarbiyah. The process of learning that takes place between the characteristic of one subject with the other subject. The condition was impressed by running in place, as an example of Learning Strategy implemented in several courses Programs Tarbiyah Especially in the Islamic Religious Education Prodi third semester of 2010. The lecturer used the same learning strategy in teaching learning process or one subject to another subject. Researcher focused on the subject of Learning Strategy and Tafsir-I as a comparison. Based on the background the research formulated the problem is How Application of Learning Strategies, Learning Methods, and Learning Media are implemented in Lhokseumawe Malikussaleh STAIN Education Programs Tarbiyah Prodi third semester student of Islamic Religion? The purpose of this study was to determine Learning Strategy, Learning Methods, and Learning Media are held on Malikussaleh STAIN Lhokseumawe Tarbiyah Program in third semester students. This research is qualitative approach. It describes and explains the data found in the field. To analyze the data by using the technique of data reduction. As a result found that the learning strategy was held on Tafsir-I course is expository and inquiry strategies subsequently combining it with methods such as discussions and question and answer. In teaching learning process the lecturers less used of media such as books, markers, pens and blackboard. The implementation of learning strategy on Learning Strategies course lecturers tend to use Cooperative Learning Strategies and combine it with demonstration method, question and answer. In addition, lecturers also take advantage of instructional media including books, pens, markers and whiteboard.